2017
DOI: 10.7150/thno.20512
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-647 Targets SRF-MYH9 Axis to Suppress Invasion and Metastasis of Gastric Cancer

Abstract: MicroRNAs (miRNAs) play important roles in regulating tumour development and progression. Here we show that miR-647 is repressed in gastric cancer (GC), and associated with GC metastasis. Moreover, we identify that miR-647 can suppress GC cell migration and invasion in vitro. Mechanistically, we confirm miR-647 directly binds to the 3' untranslated regions of SRF mRNA, and SRF binds to the CArG box located at the MYH9 promoter. CCG-1423, an inhibitor of RhoA/SRF-mediated gene transcription, inhibits the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 46 publications
(53 reference statements)
2
74
0
Order By: Relevance
“…Herein, we found that circRHOBTB3 contained the binding sites of miR-654-3p predicted by bioinformatic website circinteractome and verified there was direct binding relationship between circRHOBTB3 and miR-654-3p using biotinylated-nucleic probe pull down assay and luciferase reporter experiments, which suggested that circRHOBTB3 might serve as a sponge for miR-654-3p to inhibit the proliferation of GC. MiRNAs have been shown to be a large family of gene regulator that negatively regulate their target mRNAs in a sequence-specific manner and its role in cancers have been extensively studied [31,42,43]. Numerous evidences have confirmed that miRNAs play essential roles in multiple biological process related to cancer, including cell differentiation, proliferation, tumorigenesis, angiogenesis, invasion, and metastasis [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we found that circRHOBTB3 contained the binding sites of miR-654-3p predicted by bioinformatic website circinteractome and verified there was direct binding relationship between circRHOBTB3 and miR-654-3p using biotinylated-nucleic probe pull down assay and luciferase reporter experiments, which suggested that circRHOBTB3 might serve as a sponge for miR-654-3p to inhibit the proliferation of GC. MiRNAs have been shown to be a large family of gene regulator that negatively regulate their target mRNAs in a sequence-specific manner and its role in cancers have been extensively studied [31,42,43]. Numerous evidences have confirmed that miRNAs play essential roles in multiple biological process related to cancer, including cell differentiation, proliferation, tumorigenesis, angiogenesis, invasion, and metastasis [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that circRNAs mainly function as miRNA sponge to sequester miRNA and then regulate subsequent gene expression [30,31]. To investigate whether circRHOBTB3 served as "miRNA sponge" in GC cells, we selected the eleven top potential binding miRNA (miR-244, miR-494, miR-548p, miR-570, miR-586, miR-600-3p, miR-619-3p, miR-654-3p, miR-1200-5p, miR-1265-5p, miR-1305) with a context score percent-ile≥90 predicted by CircInteractome database.…”
Section: Circrhobtb3 Acted As a Molecule Sponge For Mir-654-3pmentioning
confidence: 99%
“…The S100A4‐MYH9 axis could promote migration and invasion through inducing transforming growth factor‐β‐mediated epithelial‐mesenchymal transition in gastric cancer 35 . In addition, MYH9 was downregulated by miR‐124, miR‐647, or let‐7f to suppress invasion and metastasis in colorectal or gastric cancer 36‐38 . It is well known that the Wnt/β‐catenin signaling can promote metastasis and is associated with poor progression in a variety of cancer types, including NPC 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have revealed that the dysregulation of miRNAs is strongly associated with the tumorigenesis and progression of cancers, including GC [16-18]. Additionally, miRNAs have been reported to be used as biomarkers of diagnosis [19] and prognosis [20, 21] in GC.…”
Section: Discussionmentioning
confidence: 99%